Hydraulic fracturing in earth-rock fill dams - Wang, Jun-Jie.; Jiaotong, Chongqing; Wiley eBooks (Singapore : Wiley, 2014)
Presents a systematic and comprehensive study of hydraulic fracturing, original in its concentration of core soil problems There have been a number of well-studied cases in which dams have failed or been damaged by concentrated leaks for no apparent cause. In some of these experiences, investigators concluded that differential settlement cracks were the probable causes, even though no cracks were seen on the surface. In these examples, it was not determined whether the crack was open before the reservoir filled or whether it might have opened afterw.
5.2 Experimental Technique5.2.1 Loading Assembly; 5.2.2 Calculation Theory; 5.2.3 Testing Procedures; 5.2.4 Test Program; 5.3 Testing Results; 5.4 Fracture Failure Criteria; 5.5 Discussions; 5.5.1 Testing Technique; 5.5.2 Failure Criteria; 5.6 Summary; References; Chapter 6 Hydraulic Fracturing Criterion; 6.1 Introduction; 6.2 Failure Criterion; 6.2.1 Simplification of a Crack; 6.2.2 Criterion; 6.3 Cubic Specimen with a Crack; 6.3.1 Calculation of KI; 6.3.2 Calculation of KII; 6.3.3 Calculation of (KI2 + KII2)0.5; 6.3.4 Dangerous Crack Angle; 6.4 Core with a Transverse Crack.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Earth dams; Dam failures; Hydraulic fracturing; Dam failures; Earth dams; Hydraulic fracturing; TECHNOLOGY & ENGINEERING -- Hydraulics; Dam failures; Earth dams; Hydraulic fracturing; Electronic books